Transcranial magnetic stimulation in psychiatry - Marcolin, Marco Antonio (2012)
Objective: The objective of this article was to describe the experience with Transcranial Magnetic Stimulation at the Institute of Psychiatry of the Hospital das Clínicas of the Medical School of the University of São Paulo (HC-FMUSP), and its application in psychiatric clinical practice. Methods: A general description of the principles and history of Transcranial Magnetic Stimulation (TMS) was provided. Furthermore, the main results of research conducted by us over 13 years in areas such as depression, schizophrenia, obsessive-compulsive disorder, chemical dependency, cognitive impairment, childhood (autism), among others, were compiled. Issues related to safety and side effects of importance for clinical practice are also addressed. Results: These are addressed together with the main studies presented in the body of the text. Conclusion: TMS is a procedure with multiple therapeutic indications in psychiatric and neurological disorders, in addition to having diagnostic potential and usefulness in neurosurgical planning. It is currently approved by the Federal Council of Medicine for the treatment of depression and auditory hallucinations, regardless of research protocols. It is an innovative method in its technical aspects: non-invasive, focal and painless stimulation, simple to apply and with low risk for research in human beings, in addition to a benign profile of side effects.